2014
DOI: 10.11005/jbm.2014.21.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Undertreatment of Osteoporosis Following Hip Fractures in Jeju Cohort Study

Abstract: BackgroundOsteoporosis treatment following hip fracture is well known to not enough. We previously performed intervention study for orthopaedic surgeon's education and reported twofold increase in osteoporosis detection and treatment rate observed between 2005 and 2007. This follow-up observational study was conducted to find out the rate in which a diagnostic workup and treatment for osteoporosis were done in patients with hip fracture.MethodsMedical records and radiographs in patients who were older than 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
2
11
0
2
Order By: Relevance
“…As a result, male osteoporosis is likely to be underestimated. 3 13 18) The current study confirmed that males were more underdiagnosed and undertreated than females for osteoporotic fracture.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As a result, male osteoporosis is likely to be underestimated. 3 13 18) The current study confirmed that males were more underdiagnosed and undertreated than females for osteoporotic fracture.…”
Section: Discussionsupporting
confidence: 78%
“…Several reports suggested that awareness of orthopedic surgeon reduces the risk of osteoporotic fracture and education is the way to improve management for osteoporosis. 3 10 23 25) However, public management program could be a possible solution. 5 10 23) Singh et al 5) reported the screening and treatment for osteoporosis reduced the incidence of proximal humeral fracture by the osteoporosis prevention and management program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos apontam que grande parte da população mundial é acometida por uma delas ou por ambas, principalmente as mulheres pós-menopausa e os idosos acima de 70 anos. Estima-se que uma porcentagem significativa dos acometidos vem a óbito após complicações pós-cirúrgicas ou longos períodos de imobilização (16,17,22,48,49).…”
Section: Osteoporose E Osteoartriteunclassified
“…A alteração de perfil populacional ligada ao aumento de idosos vem gerando problemas sociais e econômicos ao idoso e ao Estado. Muitos acometidos pela OA e OP vem a óbito após longos períodos de imobilização ou devido às complicações de cirurgias que visam amenizar sua situação (16,21,22).…”
Section: Introductionunclassified